The effect of wick structure and filling ratio to the vapour chamber performance in electronic cooling system using an experimental method / Fairosidi Idrus ... [et al.] - Idrus, Fairosidi; Yaakob, Yusli; Abdul Razak, Muhammad; Mohamed, Mazlan; Abd. Razak, Azli; Abdullah, Mohd Zulkifly; Abdullah, Muhammad Khalil (Universiti Teknologi MARA Pulau Pinang, 2011)
The need for higher performance of electronic device becomes very important presently. The heat dissipated from the device at high flux demand better cooling system for heat removal in order to maintain performance and reliabilty of the electronic device.